Nonlinear relationship between fibrinogen-to-albumin ratio and mortality in critically ill patients with sepsis: a retrospective cohort study - Jiang, Daishan; Yuan, Xiaoyu; Shen, Yanbo; Bian, Tingting (Frontiers in Nutrition, 2025)
BackgroundThe fibrinogen-albumin ratio (FAR) is recognized as a prognostic biomarker in several diseases, but its role in sepsis remains controversial. To elucidate the relationship between FAR and mortality risk in a large cohort of patients with sepsis.MethodsIn this retrospective cohort study, we analyzed clinical data from the Medical Information Mart for Intensive Care IV Database (version 2.2) to investigate the mortality of sepsis patients. We employed restricted cubic spline curves and Cox regression models to evaluate the effect of FAR on mortality and conducted subgroup analyses to verify the consistency of our primary findings.ResultsIn our analysis of 4,615 sepsis patients, we observed that mortality risk initially decreased with increasing FAR values, reaching a minimum at approximately 94.5*10−3, before rising again. Cox regression analysis revealed differing hazard ratios (HRs) for FAR quartiles relative to the second quartile (Q2). At 28 days, adjusted HRs were 1.23 (95% CI: 1.03–1.46) for Q1, 1.14 (0.96–1.36) for Q3, and 1.11 (0.93–1.33) for Q4. By 90 days, these HRs adjusted to 1.25 (1.07–1.46) for Q1, 1.21 (1.04–1.41) for Q3, and 1.21 (1.03–1.42) for Q4. This pattern persisted at 1-year mortality, with HRs of 1.16 (1.00–1.33) for Q1, 1.22 (1.06–1.39) for Q3, and 1.24 (1.07–1.43) for Q4.ConclusionFAR exhibited a nonlinear, U-shaped association with mortality risk at 28 days, 90 days, and 1 year in patients with sepsis. These findings suggest that FAR may serve as a practical prognostic biomarker to support early risk stratification and clinical decision-making in sepsis care.